Understanding Kashmir and Kashmiris - Snedden, Christopher (London Hurst & Company, 2015)
Examines the strategic and historical circumstances surrounding the British creation and handing over of the Princely State of Jammu and Kashmir, the Maharaja's accession to India, and the unintended consequences of these actions.
Include Index, Bibliography, Glossary and Maps
Keywords: India--Jammu and Kashmir -- Diplomatic relations -- Politics and government